PELAYANAN KESEHATAN PADA ANAK TUKANG “SUUN” DI YAYASAN LENTERA ANAK BALI KOTA DENPASAR - I Gede Yudiana Putra; Ni Putu Eka Febianingsih; I Kadek Agus Dwijaputra (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2022)
Background: Unfortunate Children such as street children in Denpasar must work to survive. One of the jobs they can do were to become hawkers and become a